1996
DOI: 10.3109/03009749609069218
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Carpal Tunnel Syndrome Secondary to Tophaceous Compression of the Median Nerves

Abstract: A 65-year-old man with long-term gouty arthritis developed bilateral carpal tunnel syndrome. At surgery a chalky substance, which showed negative birefringence on polarized microscopy, was found infiltrating around the intensely inflamed transverse carpal ligaments. In differential diagnosis of carpal tunnel syndrome, tophaceous compression over the median nerve should be taken into consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 2 publications
0
5
0
3
Order By: Relevance
“…In this study, we found a prevalence of 20% for symmetric PNP and 20% for MMNP, both being most frequent in SLE (50%), followed by RA (50%), fibromyalgia (40%), and gout (25%). To our knowledge, there are no previous reports on PNP in patients with gout except for some anecdotal evidence that gout could increase the risk of tophi‐related mononeuropathies at the wrists and elbows . We reported previously that patients with gout had a higher peripheral neuropathy frequency (65.4%) and the presence of systemic neuropathy is around of 31.5%; the variables associated with PN were higher disability, higher number of tophi, higher age, lower education level, and higher frequency of severe tophaceous gout…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In this study, we found a prevalence of 20% for symmetric PNP and 20% for MMNP, both being most frequent in SLE (50%), followed by RA (50%), fibromyalgia (40%), and gout (25%). To our knowledge, there are no previous reports on PNP in patients with gout except for some anecdotal evidence that gout could increase the risk of tophi‐related mononeuropathies at the wrists and elbows . We reported previously that patients with gout had a higher peripheral neuropathy frequency (65.4%) and the presence of systemic neuropathy is around of 31.5%; the variables associated with PN were higher disability, higher number of tophi, higher age, lower education level, and higher frequency of severe tophaceous gout…”
Section: Discussionmentioning
confidence: 81%
“…To our knowledge, there are no previous reports on PNP in patients with gout except for some anecdotal evidence that gout could increase the risk of tophi-related mononeuropathies at the wrists and elbows. [47][48][49][50][51][52][53][54][55] We reported previously that patients with gout had a higher peripheral neuropathy frequency (65.4%) and the presence of systemic neuropathy is around of 31.5%; the variables associated with PN were higher disability, higher number of tophi, higher age, lower education level, and higher frequency of severe tophaceous gout. 56 We are not aware of any other study reporting systemic neuropathy in patients with gout.…”
Section: Discussionmentioning
confidence: 99%
“…Sur 439 cas (654 mains) de SCC publiés par Phalen jusqu'à 1966, deux cas seulement avaient été déclenchés par des dépôts d'urate [13]. Dans une révision de la littérature jusqu'à 1996, Tsay et al retrouvèrent 35 cas [14].…”
Section: Discussionunclassified
“…Plus rare est la compression du nerf cubital par tophus, décrite toujours au niveau du coude [14][15][16]. La compression de ce nerf au canal de Guyon, isolé ou concomitant avec un SCC, comme dans notre premier cas, n'a pas été retrouvée dans la littérature.…”
Section: Discussionunclassified
“…Electrophysiological studies have also demonstrated peripheral neuropathy in 39% of patients with RA and in 11% of patients with SS; some of these patients have subclinical or asymptomatic disease. In gout, there are reports of peripheral neuropathy due to compression secondary to tophi …”
Section: Introductionmentioning
confidence: 99%